The Social Impact of Sports Extracurricular Development at SMPN 1 Palangka Raya - Ujen Zenal Mikdar; Endang Handayani; Zuly Daima Ulfa; Roso Sugiyanto (Universitas Pendidikan Indonesia (UPI), 2022)
Introduction: As a social phenomenon in society, especially in schools, the emergence of a moral decline experienced by society is a sign of the decline and destruction of the nation. On the other hand, morality is an important factor for the development of the identity and character of a nation's society, so the participation of the school community is needed in reducing this decline. Purpose: To describe the social impact of organizing extracurricular sports at SMPN 1 Palangka Raya. Methods: This research is also descriptive qualitative research, with subjects and informants being sports teachers as coaches of sports extracurriculars and students' parents, as well as the principal of SMPN 1 Palangka Raya. While the sports of choice for students participating in extracurricular sports are 15 table tennis, 84 basketball, 34 karate, 68 badminton, 67 football, 39 martial arts, 29 volleyball, and 16 chess, Results: The results of this study prove that there are social impacts, both positive and negative. Positive impacts, namely (1) can build student character, including being able to develop an attitude of cooperation, hard work, responsibility, discipline, enthusiasm, helping each other, and getting along with fellow students despite different ethnicities, races, religions, and even cultures; (2) can channel students' sports interests and talents; (3) can build a school's